Effects of ethanol and protein deficiency on pancreatic digestive and lysosomal enzymes. Issue 2 (February 1995) - Apte, M V; Wilson, J S; Korsten, M A; McCaughan, G W; Haber, P S; Pirola, R C
Abstract : The pathogenesis of alcoholic pancreatitis is not fully understood. An increase in pancreatic digestive and lysosomal enzyme synthesis because of ethanol consumption could contribute to the development of pancreatic injury in alcoholics. This study aimed, firstly, to determine the effect of ethanol on the content and messenger RNA levels of pancreatic digestive enzymes and on the messenger RNA level of the lysosomal enzyme cathepsin B, and secondly, to examine the influence of concomitant protein deficiency (a known association of alcoholism and pancreatic injury) on these effects. A rat model of chronic ethanol administration was used in which rats were fed in groups of four, and for four weeks, protein sufficient and protein deficient diets with or without ethanol. Ethanol increased the pancreatic content of lipase but did not influence chymotrypsinogen or trypsinogen values. mRNA levels for lipase, trypsinogen, and chymotrypsinogen were raised in rats fed ethanol. Protein deficiency resulted in reduced tissue levels of lipase, chymotrypsinogen, and amylase but did not influence trypsinogen values. mRNA levels for proteases were increased in protein deficient rats, while those for lipase remained unaltered. Both ethanol and protein deficiency increased mRNA levels for cathepsin B. It is concluded that chronic ethanol consumption, in both protein sufficient and protein deficient states, increases the capacity of the pancreatic acinar cell to synthesise digestive and lysosomal enzymes.